Diversity in modern heart failure trials: Where are we, and where are we going. (1st February 2022) - Anaba, Uzoma; Ishola, Abiodun; Alabre, Alisha; Bui, Albert; Prince, Marloe; Okafor, Henry; Kola-Kehinde, Onaopepo; Joseph, Joshua J.; Mitchell, Darrion; Odei, Bismarck C.; Uzendu, Anezi; Williams, Karen Patricia; et al.
Abstract: Over the last three decades, increased attention has been given to the representation of historically underrepresented groups within the landscape of pivotal clinical trials. However, recent events (i.e., coronavirus pandemic) have laid bare the potential continuation of historic inequities in available clinical trials and studies aimed at the care of broad patient populations. Anecdotally, cardiovascular disease (CVD) has not been immune to these disparities. Within this review, we examine and discuss recent landmark CVD trials, with a specific focus on the representation of Blacks within several critically foundational heart failure clinical trials tied to contemporary treatment strategies and drug approvals. We also discuss solutions for inequities within the landscape of cardiovascular trials. Building a more diverse clinical trial workforce coupled with intentional efforts to increase clinical trial diversity will advance equity in cardiovascular care. Highlights: Recent events lay bare the potential continuation of historic inequities in available heart failure clinical trials Cardiovascular disease (CVD) has not been immune to these disparities Building a more diverse clinical trial workforce will advance equity in cardiovascular care Intentional efforts geared towards increasing clinical trial diversity will advance equity in cardiovascular care.